Cultivating Intellectual-Mental Character through Islamic Moral Education: The Strategic Role of Aqidah Akhlak Teachers - Ainul Ikrom; Kholilur Rahman; Imam Mashuri (Journal of Educational Management Research, 2026)
This study aims to analyze the role of Aqidah Akhlak teachers in developing students’ intellectual-based character and to identify the supporting and inhibiting factors influencing the character formation process. The study employed a descriptive qualitative approach. Data were collected through qualitative research procedures and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation. The findings reveal that Aqidah Akhlak teachers play several essential roles in intellectual-based character development, namely as role models (*uswatun hasanah*), character and moral builders, mentors and guides, educators in the digital era, and facilitators of learning through habituation practices. Intellectual-based character formation is implemented through positive daily habits, exemplary behavior, and discussion and question-and-answer methods that encourage students’ critical thinking skills. Supporting factors include teachers’ exemplary conduct and a religious and conducive school environment. Meanwhile, the main inhibiting factors are students’ lack of discipline, negative peer influences outside school, and insufficient supervision from parents and teachers. The study implies that strengthening teachers’ educational roles and fostering collaboration among schools, families, and communities are essential for promoting sustainable intellectual and moral character development among students.